Chlorophyll a content of the benthic foraminifera Amphistegina lobifera exposed to electric current, April 2023 - Rebecchi, Federica; Lattanzi, Davide; Abramovich, Sigal; Ambrogini, Patrizia; Frontalini, Fabrizio; Schmidt, Christiane (In: Rebecchi, F et al. (2025): Effects of electric current on growth, chlorophyll a content, pulse amplitude modulation response, and new chamber formation of the foraminifera Amphistegina lobifera [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983600, 2025)
This dataset contains measurements of chlorophyll a content, quantified by determining a change in the total pigments of the endosymbionts of the benthic foraminifera Amphistegina lobifera, exposed to electric currents over a one-month period. The data were collected in April 2023, the first of a two-part experiment, using a Tecan Spark plate reader operated with SparkControl v2.3. This dataset provides insights into the effects of electric currents on the physiological responses of the diatom symbionts of Amphistegina lobifera.
Keywords: Benthic foraminifera; chlorophyll-a; electric current; growth rate; Laboratory experiment; PAM fluorometry